Analysis of the Influence of Motivation and Work Environment on the Performance of Teaching Staff at Methodist High School in Berastagi - Parhusip, Ramania Sthefany Rolenta; Lubis, Irsad (Manunggal Halim Jaya, 2024)
Based on the initial survey, deficiencies in the performance of teaching staff were identified, as indicated by high absenteeism rates, which ultimately negatively impact the school's performance. This study focuses on the aspects of motivation, work environment, and the performance of teaching staff, examining whether motivation and the work environment affect teaching staff performance both separately and collectively. The aim of this research is to understand the conditions of motivation, work environment, and teaching staff performance at SMA Swasta Methodist Berastagi, and to assess the impact of motivation and work environment on teaching staff performance, both partially and simultaneously. The results show that motivation and the work environment are rated as good, as is the performance of the teaching staff. Motivation contributes 12.04% to teaching staff performance, while the work environment has an 8.88% impact. Together, motivation and the work environment influence teaching staff performance by 37.6%. The recommendations of this study emphasize the importance of meeting the need for security, as the institution has not provided sufficient future guarantees for the teaching staff. One solution is to offer retirement programs or old-age benefits. Additionally, there is a noted lack of social interaction among teaching staff, which should be improved to support their social needs. The combination of motivation and work environment contributes 37.6% to teaching staff performance, and improvements can be made by enhancing future security and increasing social interaction among the staff.